Genome-wide identification and functional characterization of magnesium transporter (MGT) gene family in soybean (Glycine max L.) and their expression profiles in response to aphid infestation, dehydration, and salt stresses - Nasrin Akter; Md Shohel Ul Islam; Fatema Tuz Zohra; Raihan Ur Rahman Ratno; Md. Shahedur Rahman; Shaikh Mizanur Rahman; Md. Abdur Rauf Sarkar (PLoS ONE, 2025)
The divalent cation, Magnesium (Mg2+), is an essential mineral element for plant growth and development. Magnesium transporter (MGT) plays a vital role in maintaining Mg2 + homeostasis within plant cells. Although extensive research has been conducted in several crop species, no comprehensive study has yet been carried out on the MGT gene family in soybean (Glycine max L.), an economically valuable oil crop species. In this study, a total of 29 MGT genes encoding proteins (GmMGT) were identified in the soybean genome through comprehensive bioinformatics analysis. The GmMGT proteins were subsequently categorized into MRS2, CorA, and NIPA groups, with the majority predicted to be localized to the plasma membrane. Analyses of gene structures, conserved domains, and motifs indicated strong structural and functional similarities across the subgroups. Gene duplication, selection pressure, and synteny analyses demonstrated that GmMGT genes had undergone purifying selection, with only 12 segmentally duplicated gene pairs being identified. Gene ontology (GO) analysis revealed the involvement of all GmMGT genes in organism localization and ion transportation. Cis-acting regulatory element (CAREs) analysis identified 53 CAREs involved in light responsiveness, tissue-specific, phytohormone, and stress responses. Notably, nine major CAREs were abundantly found in the promoter regions of GLYMA.06G159100 and GLYMA.10G180200. Through the promoter analysis, we identified 81 miRNAs and 29 transcription factor families (TFFs), overrepresented under different stress conditions. RNA-seq data from 14 different soybean tissues demonstrated higher expression in flower tissue and lower levels in nodules with GLYMA.05G168200, GLYMA.10G180200, GLYMA.12G030100, GLYMA.12G168000, GLYMA.16G003900, GLYMA.20G210300 exhibiting elevated expression patterns. Transcriptomic analysis further revealed that, 10 GmMGTs were upregulated under biotic stress at 4h, 8h, 24h, and 48h after aphid infestation, with GLYMA.02G285600 and GLYMA.13G368400 being the most upregulated genes. Under abiotic stresses, GLYMA.03G159400, GLYMA.05G196600, and GLYMA.15G125900 were upregulated in response to dehydration, while GLYMA.04G005200, GLYMA.08G126600, GLYMA.10G180200 were induced at 1h, 6h, and 12h under salinity stress. These findings shed light on the versatile roles of GmMGT genes in plant growth, development and stress response, and they may serve as a valuable resource for further functional characterization of GmMGT genes within the soybean genome.